Aspects of the biochemistry and physiology of dormancy in 'Golden Delicious' and 'Granny Smith' apples - Lithauer, P. A.(Penelope Ann) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1994.